Epidemiology of Human Brucellosis among Populations in Iraq’s Provinces in 2015 - Al-Bayaa, Yasmeen J. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Brucellosis (Malta fever) is one of the zoonotic diseases that endemic in all the world, this disease has a history from 1937 in Iraq when the microorganism was first isolated via an Iraqi clinician. Objective: To demonstrate brucellosis infection among Iraqi provinces and reveal relationship between Brucellosis with seasons, residence place, gender and age of the patients. In addition to diagnosis of brucellosis from patients in Baghdad province suspects of infection by serological methods (Rose Bengal test) and culture method in diagnosis of brucellosis in human. Patients and Methods: This cross sectional study was conducted at Iraqi hospitals in different Iraqi provinces. The blood sample (serum) was obtained from 1825 patients from different age groups after reported the patient history and diagnosed clinically to have Malta fever. Results: During The study period in Iraqi provinces in 2015, One thousands and eight hundred twenty five patients were diagnosed clinically and serologically to have brucellosis infection. The infection is more predominant in rural females in the months of summer and among Iraqi Kurdistan people. In Baghdad regions the serologic test was positive in most cases (71.3%) while only 38.3% were positive for Brucella culture. Conclusion: Our results indicate that patients were contact with infected livestock or suspected infection of Brucella like: goat, sheep, cow and buffalo located in epidemiological regions in Iraq province across the study period .